Nilai-nilai Pendidikan Akhlak bagi Anak dalam Film Doraemon yang Berjudul Stand by Me - Fitri, Amelia; Wiza, Rahmi (Lembaga Yasin AlSys, 2024)
Life in this era has witnessed an increase in immoral behavior among the younger generation, given the many moral deviations that occur. Facing this challenge, efforts to cultivate character and morals in the world of education are becoming increasingly urgent. The issue of morality in the context of education continues to be a growing issue, especially when discussing the problem of immorality. Moral education, as the main foundation in developing one's ethics and morals, has a crucial role. In an increasingly developing era, the cultivation of moral education can be done through a variety of media and not only obtained from the school bench. Cartoon or animated movies are favored by children because of the interesting and entertaining character of the image or animation. Movies are not only entertainment media and political propaganda tools but also have cultural and educational roles, one of which is found in the movie Stand by me. The method applied in this research is qualitative content analysis type with primary and secondary data sources, the research instrument is the researcher himself, the data collection technique uses documentation and observation, the data analysis technique used is content analysis. The results showed that in the movie doraemon stand by me has the value of Islamic moral education values and has an impact on the value of moral education values and can be used as a learning medium. The conclusion of the movie doraemon stand by me contains 13 moral education values identified, has a positive value in it and can be used as education and the values conveyed in accordance with the teachings of Islam.